Development and innovation in a new distributed medical programme: Scottish Graduate Entry Medicine (ScotGEM) - Graham, Fiona; Dowell, Jon; Flynn, Angela; Gupta, Shalini; MacFarlane, Andrew David; O’Malley, Andrew; Scully, Robert; Sullivan, Francis Michael; Thompson, Lloyd Samuel John; Alexander, Kirsty (Frontiers in Medicine, 2025)
IntroductionAddressing the shortage of primary-care physicians, especially in remote and rural areas, is a crucial target in many countries. This article introduces the Scottish Graduate Entry Medicine (ScotGEM) programme: a compressed, tailor-made curriculum designed to equip and enthuse its graduates to practice generalist and rural medicine in Scotland, within the ethos of socially accountable medicine.MethodsThis curriculum paper describes ScotGEM in sufficient detail for the reader to translate elements to their own context. It then collates findings from evaluations, research projects and many critical discussions about the programme. This work is used to describe and evaluate the curriculum design and delivery, with a focus on the distributed aspects.ResultsThree key innovations of the curriculum are explored in detail: the Generalist Clinical Mentor (GCM) role; the year-long primary care Longitudinal Integrated Clerkship (LIC); and the Agents of Change curriculum. There are early signs that ScotGEM is encouraging generalist, rural careers within Scotland. There is also growing evidence of the benefits ScotGEM faculty and students bring to the clinical workforce in the distributed settings.DiscussionDistributed programmes require additional organization for students and faculty. Partnerships can be challenging but immensely rewarding. Healthcare partners in rural areas need to be involved early in planning and strong relationships fostered with local “champions.”